![\text{The equation }of\text{ circle: }(x-9)^2+(y-8)^2=49](https://img.qammunity.org/2023/formulas/mathematics/college/63f5pzxt58ifx9plorzlqzugvf57u6jezl.png)
Step-by-step explanation:
Given endpoints (9,1) and (9,15)
The equation of circle:
![(x-a)^2+(y-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ilekd9w5v3ytefhk3unvr8rhka2u3mptc6.png)
To find (a, b) which is the center of the circle, we will apply the midpoint formula:
![\text{Midpoint = }(1)/(2)(x_1+x_2),\text{ }(1)/(2)(y_1+y_2)](https://img.qammunity.org/2023/formulas/mathematics/college/p6enlqls7esxuc0ff1ydww89kraf76ctd3.png)
![\begin{gathered} \text{Midpoint =1/2}(9+9),\text{ 1/2(1+15) } \\ Midpoint=\text{ 9, 8} \\ \text{Center = }(a,\text{ b) = 9, 8} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/os700zj3dza9ag602tf66yw5dbwdw5vdzs.png)
To find the radius (r), we need to find the distance between the center an any of the two points.
Using (9, 8) and (9, 1)
![dis\tan ce\text{ formula= }\sqrt[]{(y_2-y_1)^2+(x_2-x_1)^2}](https://img.qammunity.org/2023/formulas/mathematics/college/uyazttyaeh0gvtneaicvvdk6bvg2x26hyt.png)
![\begin{gathered} \text{distance = }\sqrt[]{(1-8)^2+(9-9)^2} \\ =\text{ }\sqrt[]{(-7)^2+(0)^2}\text{ = }\sqrt[]{49+0} \\ \text{Distance = }\sqrt[]{49\text{ }}=\text{ 7} \\ \text{radius = 7} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dd3xqywzinw2jmx3pqavtgfk4z9ksvjxzj.png)
![\begin{gathered} Inserting\text{ the values in }(x-a)^2+(y-b)^2=r^2\text{ } \\ \text{The equation }of\text{circle: }(x-9)^2+(y-8)^2=7^2 \\ \text{The equation }of\text{ circle: }(x-9)^2+(y-8)^2=49 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/my3opyqccepdwpz8yhklf0jb4gt60hnx9i.png)